Association between dietary consumption of multiple vitamins and age-related macular degeneration: a cross-sectional observational study in the National Health and Nutrition Examination Survey 2005–2008 - Liu, Zhao; Wang, Qiuyuan; Li, Lu; Cai, ShanJun (Frontiers in Nutrition, 2024)
Purpose: Age-related macular degeneration (AMD) is one of the common causes of blindness in the elderly worldwide. Its prevention and monitoring indicators remain a key area of research. This study aims to examine the association between vitamin intake and AMD prevalence.Methods: Data from the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2008 were used for cross-sectional analysis. Logistic regression models, subgroup analyses and multicollinearity regression were employed to assess the association between vitamin intake and AMD.Results: A total of 1,627 participants were included, with 54.5% (weighted) males and 45.5% (weighted) females. Significant differences were observed in the intake of vitamins B (B1, B2, B6, and B12), E, and folic acid between the AMD and Non-AMD groups. The Non-AMD group had higher average intakes (weighted) of vitamin B1 (1.71